UNDERSTANDING THE IMPACT OF NUTRITIONAL DEFICIENCIES ON MATERNAL HEALTH IN INDIA - G.C. Premnivas (CV. Fahr Publishing, 2025)
This study investigates the impact of nutritional deficiencies on maternal health in rural India, focusing on the prevalence of anemia among pregnant women and its associated health complications. Using a mixed-methods approach, the research combines quantitative data from a cross-sectional survey with qualitative insights from in-depth interviews and focus group discussions. The findings reveal that 60% of pregnant women in rural areas suffer from anemia, with significant regional disparities, particularly in states like Uttar Pradesh, Bihar, and Madhya Pradesh. The study highlights the socio-economic and cultural barriers that hinder access to adequate nutrition and healthcare, including financial constraints, lack of education, and limited healthcare infrastructure. Despite various government programs, the effectiveness of nutritional supplementation remains limited due to poor adherence rates, largely influenced by side effects and access issues. The study concludes by emphasizing the need for targeted interventions, including improved healthcare delivery, better nutrition education, and region-specific policies to reduce maternal malnutrition. These findings are crucial for improving maternal and fetal health outcomes in India and can serve as a model for other low-income countries facing similar challenges.